Perbandingan Antara Tingkat Pengetahuan Ibu Hamil Sebelum Dan Sesudah Mengikuti Program Kelas Ibu Di Wilayah Bangsri Jepara - LATHIFA, Safira Tsaqifiani (2015)
Background: Knowledge of pregnant women included about change in the body, and a common complaint handled, mandatory inspection, cared during pregnancy and childbirth, and to knew the signs of labor and danger signs. However, previous studied have claimed that pregnant women knowledge about danger signs still enough (71.1%), less (17.8%), and both (11.1%). Lack of knowledge was known due to the small number of health facilities for counseled caused pregnant women lack information about pregnancy. Methods: The study design using Quasi-Experimental research to design one group pretest-posttest. Sample was 16 respondents consisting of pregnant women with 20-32 weeks gestation were obtained used Purposive Sampling technique. Collecting data used questionnaires about pregnancy given before and after the class mother. After got the results, the data were tested for normality and tested analysis used Paired t-test with SPSS 17. Result: The average value of knowledge of pregnant women before join pregnant women class was 74.97. The average value of knowledge of pregnant women after joining pregnant women class was 85.53. Normality test used of Shapiro-Wilk obtained results pretest value was 0.578 (>0.05) and posttest value was 0.371 (>0.05). Normally distributed data so the data is tested by statistical analysis using Paired t-test p= 0.001 be obtained (p<0.05). Conclusion: There was a meaningful comparasio between the level knowledge of pregnant women before and after joining pregnant women class in region Bangsri Jepara.